Método de caracterização do escoamento bifásico usando sensores de deformação baseados em redes de Bragg em fibras ópticas - Baroncini, Virgínia Helena Varotto (2015)
This study developed a technique to characterize the two phase flow using optical fiber Bragg grating strain sensors. These sensors have features such as small size, flexibility, allowing to accurately measure a number of parameters under adverse conditions. The sensor unit consists of optical fiber Bragg grating positioned transversely to the flow and fixed in the pipe walls. The hydrodynamic pressure applied by the liquid or air/liquid flow to the optical fiber induces deformation that can be detected by the optical fiber Bragg grating. Given that the applied pressure is directly related to the mass flow it is possible to establish a relationship using the grating resonance wavelength shift to determine the mass flow when the flow velocity is well known. For two phase flows of air and liquid there is a significant change in the force applied to fiber that is accounted for the very distinct densities of these substances. As a consequence the optical fiber deformation and the correspondent grating wavelength shift as function of the flow will be very different for an air bubble or a liquid slug allowing their detection as they flow through the pipe. Due to its versatility and multiplexing capabilities optical fiber Bragg gratings are particularly suitable for this application. The experiments were performed in a pilot plant using air-water two-phase flows, in which various operating conditions were generated and analyzed. A quasi-distributed sensing tool with 18 sensors evenly spread along the pipe is developed and characterized making possible the characterization of the flow as well as the tracking of the bubbles over a large section of the test bed. The technique developed was validated through comparisons with available empirical mechanical models and also with the wire- mesh sensor, showing good agreement with the reference values. The study allows for the future construction of sensors that can be used to assist empirical models of multiphase flows, and open up plenty of opportunities to both laboratory measurement tools as well as field applications.